Analysis of fluted natural fibre reinforced high density polyethylene roofing panel / Nurul Atiqah Mohd Ayob - Mohd Ayob, Nurul Atiqah (Institute of Graduate Studies, UiTM, 2018)
Agriculture sector contributes abundant residues such as bamboo, kenaf and coconut coir fibre. Nowadays, agriculture wastes have the potential as supplementary raw materials due to shortage of forest resources. These residue materials can be fully utilized as a new product through a combination of non-bio material such as synthetic polymer to form bio-degradable polymer composite. This study focused on analyzes the performance of fluted natural fibre reinforced High Density Polyethylene (HDPE) roofing panel using Experimental Analysis and Computer Aided Engineering Analysis. Three types of boards were produced which were Roofing Panel Bamboo Composite, Roofing Panel Coconut Composite, and Roofing Panel Kenaf Composite. Each board types were produced with two fibre ratios which were at forty (40:60) and thirty (30:70) percent. The properties investigated were density, water absorption and thickness swelling, Scanning Electron Microscopic, thermal conductivity, thermal expansion, bending strength and stiffness, tensile strength, impact, and effects of accelerated aging cycle on water absorption and tensile strength. Finite Element Analysis (FEA) was used to analyze the performance analytically. FEA covered heat transfer properties, bending strength and tensile strength. In this study, prototype roofing panel from bamboo, kenaf and coconut coir was also manufactured. The prototype was tested and compared to the industry roofing panel in terms of some physical and mechanical properties…